Determinan sosial kejadian dengue shock syndrome di Semarang - Yudi Pradipta; Ida Safitri Laksanawati; Dibyo Pramono (Berita Kedokteran Masyarakat (BKM), 2016)
Social determinants of dengue shock syndrome in SemarangPurpose This study aimed to know the social determinants related to dengue shock syndrome.Methods This study used a case control design in Semarang. Cases were dengue patients with shock syndrome diagnosed by a clinician in the hospital, and controls were dengue patients without shock syndrome. Participants were recruited using purposive sampling, and completed written informed consent to be interviewed using a questionnaire.ResultsResults showed that children aged <18 years have the highest risk of having DSS compared to other age groups. Referral system was also correlated to dengue shock syndrome.Conclusion This study recommends the clinicians to undertake appropriate diagnosis and prompt decision making to reduce the risk of more severe DHF events. The community should improve the awareness of shock syndrome by taking their children immediately to health services for examination if they have dengue symptoms in order to get the adequate treatment.